The measurement and interpretation of dietary protein distribution during a rugby preseason - MacKenzie, K.; Slater, G.; King, N.; Byrne, N. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
Evidence suggests that increasing protein distribution may be desirable to promote muscle protein synthesis (MPS) in combination with resistance exercise. However, there is a threshold above which additional protein consumption has limited benefit for MPS and may promote protein loss due to increased oxidation. This study aimed to measure daily protein intake and protein distribution in a cohort of rugby players. Twenty-five developing elite rugby union athletes (20.5 ± 2.3 years, 100.2 ± 13.3 kg, 184.4 ± 7.4 cm) were assessed at the start and end of a rugby preseason. Using a 7-day food diary the reported daily protein intake was 2.2 ± 0.7 g·kg·day-1 which exceeds daily recommendations. The reported carbohydrate intake was 3.6 ± 1.3 g·kg·day-1 which may reflect a suboptimal intake or dietary underreporting. In general, the rugby athletes were regularly consuming more than 20 g of protein; 3.8 ± 0.9 times per day (68 ± 18% of eating occasions). In addition to documenting current dietary intakes, an excess protein estimation score was calculated to determine how frequently the rugby athletes consumed protein above a known effective dose with a margin of error. 2.0 ± 0.9 eating occasions contained protein in excess of doses (20 g) known to promote MPS. Therefore, it is currently unclear whether the consumption of regular large doses of protein will benefit rugby athletes via increasing protein distribution, or whether high protein intakes may have unintended effects including a reduction in carbohydrate and/or energy intake.